Pengaruh Pemberian Pekerjaan Rumah Terhadap Prestasi Belajar Matematika Pada Peserta Didik Kelas IV Di Sekolah Dasar Subsidi Tarbiyatul Islam Sambas - Asmarita Asmarita; Eliyah Eliyah; Adnan Adnan (Cross-border, 2020)
This study uses a quantitative approach and the type of associative research. Data collection techniques using observation, questionnaires and documentation studies. The data analysis technique used is central tendency. Simple correlation and regression. The results showed that: 1) The provision of homework was classified as very good at 84.6%. Based on the data from the questionnaire results, it can be detailed giving homework with indicators: training students' discipline in learning, carrying out orders from the teacher, luring children to return to study at home. 2) Mathematics learning achievement of students at SDS Tarbiyatul Islam Sambas for the 2020-2021 academic year of 57.62% is in the 0.40-0 interval, quite good. Based on the data from the results of the questionnaire, it can be detailed with indicators of students' mathematics learning achievement, namely the UTS and UAS scores at SDS Tarbiyatul Islam Sambas for the 2020-2021 school year. 3) Giving homework does not have a significant effect on students' mathematics learning achievement at SDS Tarbiyatul Islam Sambas for the 2020-2021 school year. Based on the results of SPSS analysis, the sig value in the Anova table is 0.616, meaning Ho is accepted and Ha is rejected. It is interpreted that there is no significant effect between giving homework to learning achievement. The relationship between giving homework variable (X) to learning achievement (Y). shown by the model summary table with an R of: 0.116 or 11.6% in the "Very low" category. The contribution of the X variable to the Y variable can be seen in the R Square value in the Summary table, which is 0.14 or 1.4%, while 98.6% is influenced by other factors. The regression equation is Y= 46,032 + (0,148) X, meaning that if the value of the homework assignment variable (X) = 0, then learning achievement is worth 46,032. But if the value of giving homework increases every unit, the learning achievement will increase by every multiple of 0.148. So based on the regression equation giving homework has a positive effect on learning achievement.